2022
DOI: 10.1158/2767-9764.crc-22-0190
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Blood-based Biomarkers for Pancreatic Cancer: A Systematic Review and Meta-analysis

Abstract: Pancreatic ductal adenocarcinoma (PDAC) has a 5-year survival rate below 5%. CA19-9 is the most commonly used blood-based biomarker for PDAC in current clinical practice, despite having been shown repeatedly to be inaccurate and have poor diagnostic performance. This review aims to assess the reported diagnostic accuracy of all blood-based biomarkers investigated to date in PDAC, by directly comparing individual biomarkers and multi-biomarker panels, both containing CA19-9 and not (novel). A systematic review … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 86 publications
0
20
0
Order By: Relevance
“…There are essential method development steps (Figure 4) to establish biomarkers for a disease, namely biomarker discovery and validation. A panel of biomarkers may be used for better performance in terms of diagnostic accuracy 159–163 . In the following sections, selected research articles from the most popular subject areas of 2022 will be briefly discussed: oncology, metabolic diseases (e.g.…”
Section: In Review: Results and Discussionmentioning
confidence: 99%
“…There are essential method development steps (Figure 4) to establish biomarkers for a disease, namely biomarker discovery and validation. A panel of biomarkers may be used for better performance in terms of diagnostic accuracy 159–163 . In the following sections, selected research articles from the most popular subject areas of 2022 will be briefly discussed: oncology, metabolic diseases (e.g.…”
Section: In Review: Results and Discussionmentioning
confidence: 99%
“…Monitoring of S100P levels may also be a useful predictor of tumor response to treatment with the experimental drug QN-302. The potential advantages of S100P as a biomarker in PDAC diagnosis have been extensively documented [ 33 , 34 , 35 , 36 , 37 , 39 ], comparing favorably to CA19-9 antigen, which can produce both false positive and false negative indications of disease [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The complete gene sequence contains 4493 nucleotides. The program QGRS Mapper [ 45 ] ( ), accessed on 12 June 2022 was used to locate putative quadruplex sequences in both sense (coding) and antisense (template) strands of the complete S100P gene. A cut-off of a maximum loop size of 12 nucleotides was used in the searches.…”
Section: Methodsmentioning
confidence: 99%
“…As these copy number values were generated via high-throughput sequencing methods, it was not necessary to control for batch effects across these data. Indeed, a recent systematic review and meta-analysis of 250 studies showed that the variability introduced by patient-to-patient comparisons is much larger than any variability that could be introduced by the different high-throughput platforms used across these studies [ 43 ]. Significant differences in the survival between the quartiles are noted where the Logrank test p -value <0.05.…”
Section: Methodsmentioning
confidence: 99%